Globalization of the acting profession: how multiculturality influences the methodology of the game - Kotyk, Iryna (Global Prosperity, 2025)
Abstract. Globalization expands the space of acting, transforming multiculturalism from an external basis into an internal structural element of the game methodology. The aim of the article was this find out how the specificity of the multicultural environment and linguistic diversity transform acting technique. An interdisciplinary approach was used (cultural, theater studies, communicative-pragmatic), comparative analysis of acting schools (American, European traditions of B. Brecht and I. Bergman, Japanese forms of no / kabuki, Indian Natya literature, Korean bodily practices), content analysis and systematization of empirical observations. The key factors of multicultural interaction (contextualization, flexibility of style, technologicality, identity) were outlined. It is proven that linguistic diversity shapes speech technique, intonation-rhythmic pattern, voice identity, and nonverbal interaction. Distinct philosophies of corporeality and emotionality in different schools are identified and the mechanisms of their hybridization are described. A structural model of the actor’s intercultural competence is proposed (cognitive, communicative, emotional-empathic, behavioral-adaptive, ethical, identification, creative-interpretative components. A set of recommendations for the modernization of educational programs (integration of intercultural competence, multidisciplinary modules, development of linguistic / paralinguistic ability, ethics of stage intimacy and safety, VR/AR digital laboratories, reflection of cultural identity, criteria of multicultural effectiveness) is formulated, which increase the quality of training and international competitiveness of actors.